2020
DOI: 10.1158/1535-7163.mct-19-0996
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combination Approach Targeting an Enhanced Protein Synthesis Pathway in MYC-driven (Group 3) Medulloblastoma

Abstract: The MYC oncogene is frequently amplified in patients with medulloblastoma, particularly in group 3 patients, who have the worst prognosis. mTOR signaling-driven deregulated protein synthesis is very common in various cancers, including medulloblastoma, that can promote MYC stabilization. As a transcription factor, MYC itself is further known to regulate transcription of several components of protein synthesis machinery, leading to an enhanced protein synthesis rate and proliferation. Thus, inhibiting enhanced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…MTOR signaling is one of the key oncogenic pathways which is often deregulated in MYC-driven cancers, including NB [ 20 ]. Moreover, it has been shown that MYC proteins and the mTOR pathway cooperate with each other at the transcription and translation levels, respectively, to elevate overall protein synthesis rate, leading to increased cell proliferation and cancer progression [ 21 , 22 , 27 ]. These pathways, either working individually or together, can cause cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MTOR signaling is one of the key oncogenic pathways which is often deregulated in MYC-driven cancers, including NB [ 20 ]. Moreover, it has been shown that MYC proteins and the mTOR pathway cooperate with each other at the transcription and translation levels, respectively, to elevate overall protein synthesis rate, leading to increased cell proliferation and cancer progression [ 21 , 22 , 27 ]. These pathways, either working individually or together, can cause cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…While our data show that although individual or concomitant inhibition of BET/mTOR has greater antitumor efficacies against MYCN-amplified NB cells, the combination also efficiently inhibits cell growth and induces apoptosis in non-MYCN-amplified NB cells, pointing to a broader relevance of our combined approach in NB. Because non-MYCN-amplified NB cell lines, including SK-N-AS, express MYC [ 29 ] which is a target for combined BET/mTOR in medulloblastoma cells [ 22 ]. MYC may be a secondary target for these inhibitors in the context of NB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations